Química experimental: uma abordagem investigativa do teor de ferro em alimentos por espectrofotometria - Dias, Estela de Lima (2020)
Practical activities in the laboratory are guided by script with traditional procedures, and in order to carry out the experiments, it is necessary to follow a linear sequence, which the professor or text direct what and how to do. The aim of this work is to put the student on a position to carry out research, using concepts, develop skills, attitudes and values. The students assumed the role of researcher, reflecting critically on their way of thinking and acting. The teachers' role in this construction was to problematize the phenomena, question the students and the data, make relationships, contextualize the learned content, and stimulate the creativity and involvement of the students. Experimentation by an investigative approach was adopted, which is one of the ways to promote Scientific Literacy, which, briefly, prepare students for life in society, taking into account their citizen, critical and responsible activity. The progress and application of this project were analyzed through systematic observation and by categorizing the data obtained in the application of diagnostic questionnaires, according to the consulted references. At the end of the completed project, the investigative activity of analysis of iron in food by ultraviolet spectrophotometry has developed research habilities, and scientific communication among students supported by the articulation of knowledge already acquired. It also had possibilited training new studies, stimulating the performance of team activities and cooperation between the students involved, in addition to prepare them for the professional activities of chemistry technician.